Vibration separation technique based localized tooth fault detection of planetary gear sets: A tutorial. (15th August 2019) - Guo, Yu; Zhao, Lei; Wu, Xing; Na, Jing
Highlights: The vibration separation technique is surveyed. A scheme for tooth-root crack detection of planetary gearboxes is designed. Improvement on the data sections connection is proposed. Abstract: Due to the epicyclic motion of planet gears revolving around the sun gear in a planetary gear set, the vibration transfer paths between the gear-meshing positions and the outer ring gear mounted sensor are time-varying. This makes conventional localized gear faults detection approaches, such as the synchronous averaging and the narrowband demodulation, not usable for planetary gearboxes directly. The vibration separation technique was proposed more than 20 years ago to address the issue from the time-varying vibration transfer path, which allows further exploring the conventional gear faults detection approaches for the localized tooth fault detection of planetary gear sets. This tutorial is dedicated to study the vibration separation technique and showcase its application to the localized tooth fault detection of planetary gear sets. To guide readers' understanding of the localized tooth fault detection of planetary gear sets comprehensively, the conventional gear fault detection methods, synchronous averaging and narrowband demodulation, are reviewed briefly at first. Subsequently, the features of planetary gear sets for vibration analysis are introduced. Furthermore, the conventional vibration separation technique is surveyed and an improvement on synthesizing the artificial gear vibration in the vibration separation is proposed. Then, a tooth-root crack detection scheme for planet and sun gears in a planetary gear set is designed by combining the vibration separation with the synchronous averaging and the narrowband demodulation. Experiments on a planetary gearbox test rig with the tooth-root crack of a planet gear and the sun gear have been carried out. The vibration analysis results demonstrate the effectiveness of the vibration separation technique for localized fault detection of planetary gear sets. It is hoped that this tutorial would provide a helpful reference for the readers in this field.